Sample contamination explains evidence of close kin proximity in yellowfin tuna (Thunnus albacares) in the Western and Central Pacific Ocean - Anderson, Giulia; Macdonald, Jed I.; Lal, Monal; Hampton, John; Smith, Neville; Rico, Ciro (Frontiers in Marine Science, 2023)
Anderson et al.’s 2019 paper ‘Close Kin Proximity in Yellowfin Tuna (Thunnus albacares) as a Driver of Population Genetic Structure in the Tropical Western and Central Pacific’ provided observations of genetically related individuals among sampled yellowfin tuna. Resampling of some individuals from the original study produced very different sequencing results when compared with the original dataset, one possible explanation of which is cross-contamination among the original samples. Re-analyses produced no indication of strong population structure, including a very slightly and consistent heterozygosity deficit with only one statistically significant pairwise FST value of 0.002. We identified only one pair of genetically similar individuals that could still be an artefact of lingering contamination. These new results therefore support a highly connected population of yellowfin tuna in the study area, although we do not rule out the potential for local adaptation driven by non-observed loci or genetic sub-structure operating at more contemporary scales.